2018
DOI: 10.1111/cas.13508
|View full text |Cite
|
Sign up to set email alerts
|

Programmed death‐ligand 1 is a promising blood marker for predicting tumor progression and prognosis in patients with gastric cancer

Abstract: Immune checkpoint inhibitor therapy has been clinically introduced for several malignancies, and its effectiveness has been confirmed by clinical trials. In particular, programmed cell death protein 1 (PD‐1) and programmed death‐ligand 1 (PD‐L1) are widely known as important immune checkpoint molecules associated with the mechanisms of immune escape by malignant tumor cells. In addition, liquid biopsy of blood specimens has the clinical benefit of providing a simple, repeatable sampling tool. Non‐invasive liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 22 publications
0
22
1
2
Order By: Relevance
“…At present, the difficulties associated with performing biopsies hamper glioma diagnosis and therapeutic intervention, highlighting the need to discover non-invasive or minimally invasive biomarkers for early diagnosis and correct stratification (31). sPD-L1 can be detected in biofluids, providing a novel diagnostic test for a variety of tumors (32)(33)(34). In our previous study, elevated sPD-L1 levels in the serum were observed in preoperative patients with HGG.…”
Section: Discussionmentioning
confidence: 95%
“…At present, the difficulties associated with performing biopsies hamper glioma diagnosis and therapeutic intervention, highlighting the need to discover non-invasive or minimally invasive biomarkers for early diagnosis and correct stratification (31). sPD-L1 can be detected in biofluids, providing a novel diagnostic test for a variety of tumors (32)(33)(34). In our previous study, elevated sPD-L1 levels in the serum were observed in preoperative patients with HGG.…”
Section: Discussionmentioning
confidence: 95%
“…Binding of programmed death‐1 (PD‐1) and its ligands—programmed death ligand 1 (PD‐L1) and programmed death ligand 2 (PD‐L2)—on tumor or immune cells can inhibit cytotoxic T‐cell responses, allowing tumor cells to evade immune detection . Clinical trials of anti‐PD‐1/PD‐L1 antibodies have reported a high response rate and significantly improved overall survival in several malignancies …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the genomic instability that characterizes the heterogeneity of gastric cancer can be put to good use, making it a good candidate for immune therapy, owing to neoepitope presentation on cancer cell surfaces that enhances tumor immunogenicity [6,7]. A Recent study assessed the clinical significance of Programmed-celldeath protein-Ligand 1 (PD-L1) mRNA expression in blood specimens obtained from patients with gastric cancer [25]. PD-L1 mRNA expression was significantly higher in patients with advanced gastric cancer than in patients with early gastric cancer (p=0.002) [25].…”
Section: Perspectivementioning
confidence: 99%
“…A Recent study assessed the clinical significance of Programmed-celldeath protein-Ligand 1 (PD-L1) mRNA expression in blood specimens obtained from patients with gastric cancer [25]. PD-L1 mRNA expression was significantly higher in patients with advanced gastric cancer than in patients with early gastric cancer (p=0.002) [25]. In addition, PD-L1 expression correlated significantly with depth of tumor invasion, distant metastasis, and stage (p=0.001, p<0.001, and p<0.001, respectively).…”
Section: Perspectivementioning
confidence: 99%